(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article comprehensively covers the application of nuclear physics in the field of medicine. It analyzes the fundamental principles of nuclear medicine, radioactive isotopes, and the interaction of ionizing radiation with matter and biological tissues. In the field of diagnostics, SPECT and PET technologies, along with the role of radiopharmaceuticals, are reviewed in detail. In the therapy section, methods of external beam radiation (proton therapy), brachytherapy, and radionuclide therapy are described based on their scientific foundations.